The forgotten annual forbs of Victoria's basalt plains grassland. (13th June 2021) - J Sinclair, Steve; Scott‐Walker, Geordie; Batpurev, Khorloo; Morgan, John W.; Just, Karl; Cook, Damien
Abstract : Comparison of historical data with recent surveys of grasslands across Victoria's basalt plain reveals a substantial decline in native annual forbs. Eleven of the 35 species once common in this ecosystem have not been recorded for decades. The near loss of a lifeform from an ecosystem should ring alarm bells, but it seems the warning has passed largely unnoticed. Is this due to 'shifting baseline syndrome'? What has caused this quiet decline in biodiversity, and what does it teach us about management and restoration?